2018
DOI: 10.1186/s12958-018-0441-z
|View full text |Cite
|
Sign up to set email alerts
|

Villainous role of estrogen in macrophage-nerve interaction in endometriosis

Abstract: Endometriosis is a complex and heterogeneous disorder with unknown etiology. Dysregulation of macrophages and innervation are important factors influencing the pathogenesis of endometriosis-associated pain. It is known to be an estrogen-dependent disease, estrogen can promote secretion of chemokines from peripheral nerves, enhancing the recruitment and polarization of macrophages in endometriotic tissue. Macrophages have a role in the expression of multiple nerve growth factors (NGF), which mediates the imbala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 96 publications
0
43
0
2
Order By: Relevance
“…Why a transplanted or congenital ectopic endometrium develops into endometriosis is the source of much research. The causes of this development include research on the role of estrogen and estrogen receptors (ERs), the estrogen-dependent physiologic and molecular changes [71], the local levels of estrogen [71,72], the role of estrogen in macrophage-nerve interaction [72], the effects of environmental toxicants on estrogen signaling [73], and the intracellular estrogen production related to aromatase activity. In addition, the normal control of cyclic estrogen and progesterone requires activation and crosstalk of cAMP and progesterone mediated signaling pathways [74].…”
Section: Behind the Origins Of Endometriosismentioning
confidence: 99%
“…Why a transplanted or congenital ectopic endometrium develops into endometriosis is the source of much research. The causes of this development include research on the role of estrogen and estrogen receptors (ERs), the estrogen-dependent physiologic and molecular changes [71], the local levels of estrogen [71,72], the role of estrogen in macrophage-nerve interaction [72], the effects of environmental toxicants on estrogen signaling [73], and the intracellular estrogen production related to aromatase activity. In addition, the normal control of cyclic estrogen and progesterone requires activation and crosstalk of cAMP and progesterone mediated signaling pathways [74].…”
Section: Behind the Origins Of Endometriosismentioning
confidence: 99%
“…Endometriosis lesions aberrantly express a number of steroidogenic enzymes including aromatase and 17β-hydroxysteriod dehydrogenase (17β-HSD), this results in increased synthesis and decreased metabolism of estrogen (27)(28)(29) such that local levels remain high. Estrogen signaling modulates a large number of down-stream disease processes within endometriosis lesions, which are reviewed in Yilmaz and Bulun (30), Liang et al (31), and Rizner (32). Immune cell dysfunction is also intrinsically linked to the pathophysiology of endometriosis.…”
Section: Etiology and Natural Historymentioning
confidence: 99%
“…Many reports have indicated that the process of endometriosis is related to a dysregulation of the host immune and some researchers even consider EMS to be an autoimmune disorder [512]. On one hand, some studies have been focused on downregulation of anti-endometrial implants cells, such as NK cells, CD4 + /CD8 + T cells, B cells and so on [58], on the other hand, some studies demonstrated that increased immunosuppressive cells could promote the progression of endometriosis, such as Tregs (regulatory T cells), TH2 (T helper) cells and even MDSCs (myeloid derived suppressor cells), which have been suggested recently to promote the implantation of endometrial tissue [13, 14]. All these evidences pointed to the fact that the impaired immune response exists in endometriosis.…”
Section: Introductionmentioning
confidence: 99%